Experimental study on flow resistance characteristics of the uniform steam injection outflow control device - Du, Qiuying; Li, Mingzhong; Liu, Chenwei (Frontiers in Chemistry, 2023)
Introduction: Multi-point steam injection technology is a new completion method for heavy oil horizontal wells to solve the uneven distribution of the intake profile in the horizontal section. It is equipped with the flow control device to achieve the effect of balanced steam injection. Methods: The steady-state experiment method was adopted; Considering the variable mass complex flow of the steam–liquid two-phase flow in the downhole flow device, the pressure loss of downhole tools through uniform steam injection with different steam–liquid compositions was tested, the influencing factors of the pressure drop were analyzed, and a more reliable pressure drop calculation method was established. Results: The overflow pressure drop can be adjusted by changing the aperture, steam dryness, and fluid flow of the downhole outflow control device (OCD). Discussion: By comparing the experimental and theoretical results, the calculation method of the overflow resistance of single-phase and steam–liquid two-phase fluids in OCD is given, and the error is within the usable range.